Exploration and Improvement Path of Local Government Debt Risk Warning Mechanism Based on KMV Model: Taking Bengbu, Anhui as an Example - Wei, Chengtai; Shen, Mingyang; Zheng, Zizhao; Meng, Wenzheng; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
This article is based on the KMV model and explores methods for improving the local government debt risk warning mechanism under the backdrop of the pandemic, with a case study of Bengbu City in Anhui Province, China. In the context of an economic downturn and the impact of the COVID-19 pandemic, accurately understanding and effectively managing the fiscal risks of local governments is particularly important. The study focuses on analyzing the impact of changes in fiscal revenue and expenditure structures during the pandemic on local debt risks, using the KMV model for in-depth analysis. By comparing fiscal data from different time periods, the effectiveness of the existing local government debt risk warning mechanisms was evaluated. This paper also discusses how to improve risk management and proposes specific strategies and suggestions. These recommendations aim to enhance the efficacy of local government debt warning systems, especially considering the unique challenges brought about by the pandemic and economic changes. The study shows that by improving fiscal risk management and optimizing warning mechanisms, it is possible to better respond to various economic challenges that may arise in the future, providing local governments with more robust and reliable financial risk control plans.